Comparação da atividade física em adultos de Pelotas - RS por um período de cinco anos - Knuth, Alan Goularte (2008)
Physical activity has mechanisms to interfere with people's health. The health status of an individual is composed of several factors (biological, mental, social, cultural, economic) which interfere with inter-related health condition, and these determinants are in constant dynamic states producing more or less healthy. Physical activity, considered modifiable behavior, plays a role in determining the health-disease process through multiple properties, for example, in a more organic in the sense of prevention and also treatment of morbidities. The individual engaged in a systematic program of physical activity may have a protective effect against chronic diseases, and protection against mortality. On the other hand, when the disease is established, physical activity is to assist in the treatment of various morbidities. In addition to biological properties, this phenomenon is able to establish or strengthen mechanisms of social interaction, favoring the integrated approach of people and training for such mechanisms are most often experienced by children, elderly groups, among others. Thus physical activity has been increased relevance in the context of public health, and thus know its evolution and determinants may be useful for public policy for the sector. In 2002, a population-based study found a high prevalence of physical inactivity among adults in Pelotas. Such information, besides representing an important public health diagnosis, while establishing the behavior of adults in relation to lifestyle related to physical activity, warned of the need for population-based interventions, to alleviate the described. After five years no initiative has been planned in local character and the conditions for physical activity in Pelotas remain the same. In the same vein, there was no national program in the period, with the initiative to allow greater inclusion of Brazilian programs of physical activity, even if the data found in pellets look similar to the reality of the rest of the country. This study is the subject of research comparing the prevalence of physical activity in a period of five years. Another objective is to assess factors associated with physical activity now, and compare them with those found five years ago, using a methodology similar.